Post-Secondary Education in Qatar Employer Demand, Student Choice, and Options for Policy - Stasz, Cathleen (RAND Corporation, 2007)
The government of Qatar has made significant investments in post-secondary education to ensure that Qataris are able to contribute to the country's social and economic goals. The authors describe RAND's analysis of occupational demand and related post-secondary educational opportunities, and offer recommendations for improving the country's current provision of post-secondary education.